CANCEROUS DISEASES OF THE CERVIX. (Western European Journal of Medicine and Medical Science, 2026)
Advances in imaging technologies and liquid-based cytology are also discussed as key tools for improving diagnostic accuracy. Furthermore, the study explores modern prognostic models, including genomic profiling and AI-based risk stratification, which aid in predicting disease progression and tailoring individualized treatment plans. Together, these innovations represent a significant step forward in reducing the incidence and mortality associated with cervical cancer.This work highlights recent advancements in the field of cervical cancer, focusing on three critical areas: prevention, early detection, and prognostic evaluation. Emphasis is placed on the implementation of HPV vaccination programs, novel biomarkers, and molecular screening techniques that enhance early recognition of precancerous changes